Synchronization Overlap Trade-Off for a Model of Spatial Distribution of Species - Bioco, João (2021)
Despite of the widespread implementation of agent-based models in ecological modeling and another several areas, modelers have been concerned by the time consuming of these type of models. This paper presents a strategy to parallelize an agent-based model of spatial distribution of biological species, operating in a multi-stage synchronous distributed memory mode, as a way to obtain gains in the performance while reducing the need for synchronization. A multiprocessing implementation divides the environment (a rectangular grid corresponding to the study area) into stage-subsets, according to the number of defined or available processes. In order to ensure that there is no information loss, each stage-subset is extended with an overlapping section from each one of its neighbouring stage-subsets. The effect of the size of this overlapping on the quality of the simulations is studied. These results seem to indicate that it is possible to establish an optimal trade-off between the level of redundancy and the synchronization frequency. The reported paralellization method was tested in a standalone multicore machine but may be seamlessly scalable to a computation cluster.